A Model Standardisation for Anti-tuberculosis Drug Induced Heapatotoxicity - Sarita M. Kapgate; Abhijit B. Patil (Challenges and Advances in Pharmaceutical Research Vol. 8, 2022)
The goal of the study was to standardize the model of hepatotoxicity induced by ATT drugs in Wistar Albino rats. Isoniazid (INH), rifampicin (RMP), pyrazinamide (PZA), the first line drugs used in the treatment of tuberculosis (TB) associated with the potential adverse effect. ATT medications were administered to Wistar rats over the course of 4–8 weeks at a variety of doses. Nine tests in total were carried out to successfully produce hepatotoxicity. The successful attempt to induce hepatotoxicity can be achieved with the doses of INH - 100, RMP - 300, PZA - 700 mg/kg. The findings were supported by increased ALT, AST, and ALP levels when compared to baseline. The findings are also supported by histopathological changes.